2011
DOI: 10.1182/blood-2011-03-341305
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium falciparum uses a key functional site in complement receptor type-1 for invasion of human erythrocytes

Abstract: The Plasmodium falciparum adhesin PfRh4 binds to complement receptor type-1 (CR1) on human erythrocytes and mediates a glycophorin-independent invasion pathway. CR1 is a complement regulator and immune-adherence receptor on erythrocytes required for shuttling of C3b/ C4b-opsonized particles to liver and spleen for phagocytosis. Using recombinant CR1 constructs, we mapped the recognition site for PfRh4 to complement control protein modules 1 to 3 (CCP1-3) at the membrane-distal amino terminus of CR1. This regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
69
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(78 citation statements)
references
References 50 publications
7
69
0
2
Order By: Relevance
“…P. falciparum uses CR1 as an entry receptor into RBCs through binding to a parasite adhesin called PfRh4 (51,52). It has been suggested that merozoites may play a dangerous game of allowing C3 fragment deposition to occur to more readily allow PfRh4 engagement with the CR1 molecules dispersed across the RBC surface (52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…P. falciparum uses CR1 as an entry receptor into RBCs through binding to a parasite adhesin called PfRh4 (51,52). It has been suggested that merozoites may play a dangerous game of allowing C3 fragment deposition to occur to more readily allow PfRh4 engagement with the CR1 molecules dispersed across the RBC surface (52).…”
Section: Discussionmentioning
confidence: 99%
“…P. falciparum uses CR1 as an entry receptor into RBCs through binding to a parasite adhesin called PfRh4 (51,52). It has been suggested that merozoites may play a dangerous game of allowing C3 fragment deposition to occur to more readily allow PfRh4 engagement with the CR1 molecules dispersed across the RBC surface (52). Although iC3b cannot participate in the generation of MAC, it is still a ligand for CR1 (5), and the aforementioned ability of merozoite-recruited FH and FHL-1to convert C3b to iC3b would remove some of the danger associated with such an approach.…”
Section: Discussionmentioning
confidence: 99%
“…The binding site of Rh4 was mapped to CCP1 of CR‐1, and this region is known to be involved in binding C3b and C4b to accelerate decay of the C3 and C5 convertases (Park et al , 2014). In consequence, Rh4 binding specifically inhibits the convertase decay‐accelerating activity of CR‐1 (Tham et al , 2011). …”
Section: Discussionmentioning
confidence: 99%
“…However, contradictory results have been obtained regarding their association with malarial severity in different African populations (52)(53)(54)(55). CR1 interacts with two P. falciparum proteins, the malarial adhesin PfEMP1 (14) and the PfRh4 invasion ligand (15), but the binding sites have been located to the C3b and C4b binding sites of CR1, respectively (20,21). Consistent with these locations, Tetteh-Quarcoo et al (56) observed no difference between the Knops blood group variants McC a/b and Sl1/2 in the ability of the CR1 fragment CCP15-25 to interact with PfRh4 or to disrupt PfEMP1-dependent P. falciparum rosetting (56).…”
Section: Discussionmentioning
confidence: 99%
“…LHR-A contains the major C4b binding site located in CCPs 1-3, also involved in PfRh4 binding, whereas LHR-B and LHR-C contain homologous C4b/C3b binding sites in CCPs 8-10 and 15-17, which are also candidates for interaction with PfEMP1 (19)(20)(21). C1q and MBL have been proposed to bind LHR-D, but the localization of their interaction sites to particular CCP modules has not been described so far (12,13).…”
mentioning
confidence: 99%